Waste management in electroplating industry : an opportunity for metal recovery - 250992 Law, Kian Meng; Tan, Boon Sen; Norasikin Othman; The International Water Association Conference on Water & Wastewater Management for Developing Countries (2001 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2001)
10